2003
DOI: 10.1139/z03-054
|View full text |Cite
|
Sign up to set email alerts
|

Use of sulfur and nitrogen stable isotopes to determine the importance of whitebark pine nuts to Yellowstone grizzly bears

Abstract: Whitebark pine (Pinus albicaulis) is a masting species that produces relatively large, fat-and protein-rich nuts that are consumed by grizzly bears (Ursus arctos horribilis). Trees produce abundant nut crops in some years and poor crops in other years. Grizzly bear survival in the Greater Yellowstone Ecosystem is strongly linked to variation in pine-nut availability. Because whitebark pine trees are infected with blister rust (Cronartium ribicola), an exotic fungus that has killed the species throughout much o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
160
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(162 citation statements)
references
References 22 publications
2
160
0
Order By: Relevance
“…3-fold) rather than a change in bear feeding behavior, although it is possible that less winterkilled carcasses are available for bears emerging from their dens each spring due to wolf consumption; therefore, bears may need to depend more on other food sources such as elk calves Anderson 1996, Mattson 1997). Additionally, bear predation on northern Yellowstone elk calves may vary in response to the availability of whitebark pine nuts (Pinus albicaulis, a masting species) remaining from the previous summer and autumn because bears feed on these nuts after emerging from their dens each spring (Mattson et al 1991, Mattson 1997, Felicetti et al 2003.…”
Section: Cause-specific Mortalitymentioning
confidence: 99%
“…3-fold) rather than a change in bear feeding behavior, although it is possible that less winterkilled carcasses are available for bears emerging from their dens each spring due to wolf consumption; therefore, bears may need to depend more on other food sources such as elk calves Anderson 1996, Mattson 1997). Additionally, bear predation on northern Yellowstone elk calves may vary in response to the availability of whitebark pine nuts (Pinus albicaulis, a masting species) remaining from the previous summer and autumn because bears feed on these nuts after emerging from their dens each spring (Mattson et al 1991, Mattson 1997, Felicetti et al 2003.…”
Section: Cause-specific Mortalitymentioning
confidence: 99%
“…Stable isotopic analysis has become a widespread tool in ecology that can be used to infer trophic interactions and supplement insights obtained from traditional diet analysis (e.g. Hooker et al 2001, Post 2002, Felicetti et al 2003. It is possible to use carbon isotopic values to determine the relative contribution of different primary producers to a consumer's diet because primary producers (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…; Pinus albicaulis) (Blanchard and Knight 1991;Felicetti et al 2003a). My research addressed the following questions: 1) as a recognized habitat generalist, can patterns of habitat use and selection that are driven by specific habitat types be identified for wolves?…”
Section: Goals and Objectivesmentioning
confidence: 99%
“…Other studies have used stable isotope analyses to examine the diets of wild, captive, and extinct bears (Hilderbrand et al 1996;Hilderbrand et al 1999b;Hobson et al 2000;Felicetti et al 2003a;Bocherens et al 2004), but most have not examined species-specific estimates of general meat and plant consumption. Hilderbrand et al (1999a) used blood signatures from repeated captures of brown bears to examine seasonal meat intake related to body mass and composition, and concluded that meat, and particularly salmon intake, influences population density at the continental scale.…”
Section: Grizzly Bearsmentioning
confidence: 99%